Жасөспірімдердің əлеуметтік-психологиялық дамуының ерекшеліктері - Куребаева, Г.А. (My University, 2016)
There are social – psychological particulars of development of children at youthful age are examined, analysis of psychological development is ordered by different authors is given in an article. Social activity at the youthful age is examined as the fact of personal development at this age period
Keywords: the teenager; self-reflection; crisis; values of adolescents; identity; identity-feeling